-27B-14-16=-18

Add 16 to both sides of the equation.

-27B-14=-18+16

Add -18 and 16.

-27B-14=-2

-27B-14=-2

Divide each term in -27B-14=-2 by -2.

-27B-14-2=-2-2

Cancel the common factor of -2.

Cancel the common factor.

-27B-14-2=-2-2

Divide 7B-14 by 1.

7B-14=-2-2

7B-14=-2-2

Divide -2 by -2.

7B-14=1

7B-14=1

To remove the radical on the left side of the equation, square both sides of the equation.

7B-142=12

Multiply the exponents in ((7B-14)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(7B-14)12⋅2=12

Cancel the common factor of 2.

Cancel the common factor.

(7B-14)12⋅2=12

Rewrite the expression.

(7B-14)1=12

(7B-14)1=12

(7B-14)1=12

Simplify.

7B-14=12

One to any power is one.

7B-14=1

7B-14=1

Move all terms not containing B to the right side of the equation.

Add 14 to both sides of the equation.

7B=1+14

Add 1 and 14.

7B=15

7B=15

Divide each term by 7 and simplify.

Divide each term in 7B=15 by 7.

7B7=157

Cancel the common factor of 7.

Cancel the common factor.

7B7=157

Divide B by 1.

B=157

B=157

B=157

B=157

The result can be shown in multiple forms.

Exact Form:

B=157

Decimal Form:

B=2.142857‾

Mixed Number Form:

B=217

Solve for B -2 square root of 7B-14-16=-18